Potencial turístico e produção/transformação do espaço pelo turismo no município do Conde-PB - Caldas, Rosimary de Almeida (2014)
Tourism is, nowadays, an activity that generates millions in hard currency. This study sought to examine tourism not as an economic activity, but as a social, political and economic phenomenon. The municipality of Conde, located on the southern coast of Paraíba state, is a place of lush natural beauty that attract tourists from several locations. Therefore, this study aimed to discuss about the tourism potential of Conde and see how this activity has interfered with the production/processing of space and local development. For this, a matrix of tourism potential of receptive locations was applied, as well as interviews with tourists, hotels and food establishments and official agencies. During the study, despite a wide variety of attractions, it was noticed these attractions not attract, for the most part, a stream of international tourists, but its main target are the local and regional tourists. Through opinion of the visitors tourists of Conde, how is the basic infrastructure the municipality that serves not only to tourists, but the entire local community could be evaluated. The study also demonstrated a devaluation of the use of tourism as a development engine for the local community in support of growth of external agents, which have an undercover speech of improvements to the location, but no more than great entrepreneurs who bring, at the most part, negative impacts, especially with the practice of allotments and buildings in areas of environmental preservation, such as the Environmental Protection Area of Tambaba. The local government has privileged the construction of horizontal condominiums owned by business of owners of other locations, leaving the inhabitants who still have tourism as a source of income, the rest of the local population and tourists which do not stay at big resorts, without basic urban infrastructure, i.e., a policy based on the priority of a minority of high economic power at the expense of the majority of low-income.